2008
DOI: 10.1530/eje-07-0848
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase C677T polymorphism is associated with central adiposity and increased androgenicity in healthy postmenopausal women

Abstract: Objective: To assess the association of genetic polymorphisms related to cardiovascular disease (CVD) risk with anthropometric parameters and indices of androgenicity in healthy postmenopausal women. Design: Cross-sectional study in a University Menopause Clinic. Methods: The following polymorphisms were assessed in 84 healthy postmenopausal women: glycoprotein IIIa Leu33Pro, apolipoprotein E2/E3/E4, methylenetetrahydrofolate reductase (MTHFR) Ala222Val, apolipoprotein B Arg3500Gln, paraoxonase 1 Gln192Arg, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
19
0
3
Order By: Relevance
“…Postmenopause is associated with pro-atherogenic lipid profile, central adiposity, increased diastolic pressure and increased insulin resistance (1). Pro-atherogenic lipid profile is characterized in general with higher concentration of total cholesterol, LDL cholesterol, triglyceride and lipoprotein (a) (Lpa) (1,3). Furthermore, HDL cholesterol is maintained or decreased in postmenopausal women (4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postmenopause is associated with pro-atherogenic lipid profile, central adiposity, increased diastolic pressure and increased insulin resistance (1). Pro-atherogenic lipid profile is characterized in general with higher concentration of total cholesterol, LDL cholesterol, triglyceride and lipoprotein (a) (Lpa) (1,3). Furthermore, HDL cholesterol is maintained or decreased in postmenopausal women (4).…”
Section: Discussionmentioning
confidence: 99%
“…A postmenopause, a physiological state in the woman life, is associated with the increased risk for cardiovascular disease (13). Risk factors include an atherogenic lipid profile, small increases of systolic and diastolic blood pressure and increased sympathetic tone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that MTHFR Ala222Val polymorphism characterized individuals with metabolic obesity with normal weight; and is associated with elevated BMI and waist hip ratio in healthy postmenopausal women [29][30][31]. Previous researches could also elicit positive association of obesity and hypertension, coronary artery disease or liver diseases with MTH-FR C677T mutations [32][33][34].…”
Section: Discussionmentioning
confidence: 99%